Biomedicine in the Twentieth Century: Practices, Policies, and Politics - Hannaway, Caroline (IOS Press, 2013)
The editor wishes to acknowledge with gratitude the contributions of the many people and organizations that have made this volume possible. The book is based on a conference that was held at the National Institutes of Health in December 2005 to promote historical research on biomedical science in the twentieth century. The conference was conceived as a way to honor Victoria A. Harden, the founding Director of the Office of NIH History, on her retirement